ISLAM IN THE CONTEXT OF GLOBALIZATION - Shamsutdynova-Lebediuk, Tetyana (SWorld-Ger Conference proceedings, 2024)
The study is devoted to the analysis of the Muslim model of family and marriage according to modern definitions according to Sharia. Basic concepts such as aqd (marriage) and nikah (marriage according to the Sharia) are considered as key stages in the fo